(untitled) - Hewins, Ralph (Austria, 1968)
Business ethics is the study of appropriate business policies and practices regarding potentially controversial subjects including corporate governance, insider trading, bribery, discrimination, corporate social responsibility, and fiduciary responsibilities. The law often guides business ethics, but at other times business ethics provide a basic guideline that businesses can choose to follow to gain public approval.
Keywords: Đạo đức kinh doanh,Business ethics